Factors affecting the efficiency of aerosolized salbutamol delivery via a metered dose inhaler and equine spacer device. Issue 3 (4th September 2016) - Pirie, R. S.; McGorum, B. C.; Owen, C.; Carr, O.; Oakley, H.; McLachlan, G.
Abstract : Despite frequent use of metered dose inhalers (MDIs) and spacers in equine practice, limited information exists on the efficiency of aerosol delivery using such devices. We determined the particle size distribution within an MDI‐generated salbutamol aerosol delivered via an equine spacer using 'best practice' delivery technique and assessed the effect of variations in MDI use technique (shaking prior to each actuation, rapid repetitive actuations, and MDI angulation) on aerosol delivery efficiency. Under optimal conditions, only 53(±18) μg salbutamol per 100 μg actuation was delivered beyond the spacer. Although this aerosol had a high [89.6% (±2.4)] fine particle (<5 μm) fraction, and a low mass median aerodynamic diameter [2.52 (±0.29) μm], and particle size variability [geometric SD – 1.66 (±0.16) μm], within all particle size fractions, there was a high coefficient of variance (31–79%) of the percentage salbutamol delivered between experimental runs, thus impeding any effort to predict drug delivery to the patient during equine inhalation therapy. Despite observable trends and with the exception of minor statistically significant changes in the least abundant particle sizes, none of the deviations from a 'best practice' delivery technique significantly altered the relative salbutamol delivery beyond the spacer, a finding which has potential relevance with regard to maintaining user compliance.